Compassionate Conservation Clashes With Conservation Biology: Should Empathy, Compassion, and Deontological Moral Principles Drive Conservation Practice? - Griffin, Andrea S.; Callen, Alex; Klop-Toker, Kaya; Scanlon, Robert J.; Hayward, Matt W. (Frontiers in Psychology, 2020)
‘Compassionate Conservation’ is an emerging movement within conservation science that is gaining attention through its promotion of ‘ethical’ conservation practices that place empathy and compassion and the moral principles of ‘first, do no harm’ and ‘individuals matter’ at the forefront of conservation practice. We have articulated elsewhere how Compassionate Conservation, if adopted, could be more harmful for native biodiversity than any other conservation action implemented thus far, while also causing more net harm to individuals than it aims to stop. Here, we examine whether empathy, compassion and inflexible adherence to moral principles form a solid basis upon which to meet the goals of conservation biology as specified by pioneers in the discipline. Specifically, we examine a large empirical literature demonstrating that empathy is subject to significant biases and that inflexible adherence to moral rules can result in a ‘do nothing’ approach. In light of this literature, we argue that our emotional systems have not evolved to provide a reliable basis for making decisions as to how best to ensure the long-term persistence of our planet. Consequently, in its most radical form, the Compassionate Conservation philosophy should not be enshrined as a legalised guiding principle for conservation action.